Peritoneal membrane characteristics in patients on peritoneal dialysis - Sulaimani Fathia; Al-wakeel Jamal; Al-Ghonaim Mohammad; Al-Suwaida Abdulkareem; Askar Akram; Usama Saira; Feraz Niaz; Shah Iqbal; Memon Nawaz; Qudsi Abdo (Saudi Journal of Kidney Diseases and Transplantation, 2011)
Peritoneal dialysis (PD) is a well-established modality for treatment of patients with end-stage renal disease, giving excellent patient and technique survival rates. In Saudi Arabia, data collected by the Saudi Center for Organ Transplantation showed that in 2008, patients on PD accounted for a mere 4.8% of total patients on renal replacement therapy, including hemodialysis and renal transplantation. This study was conducted to identify the characteristics of membrane per-meability in the Saudi population and to assess the role of various factors affecting solute transport across the peritoneal membrane. We followed up a total of 52 patients on Continuous Ambulatory Peritoneal Dialysis (CAPD) as well as Automated Peritoneal Dialysis (APD), being treated in the PD unit of the King Khalid University Hospital, Riyadh. There were 30 female and 22 male patients; 14 patients were using CAPD while 38 patients were on APD. The mean age of the patients was 50.5 years, with a range of 14-86 years. The average body mass index (BMI) was 27.1 kg/m 2 and the mean body surface area (BSA) of the study patients was 1.71 m 2 . A standardized PET test was performed on all patients, 4-6 weeks after initiation of regular PD. The Kt/V and creatinine clearance measured 6-8 weeks after initiation of dialysis were 1.96 and 56.59 L/week, respectively. Residual renal function was assessed on the basis of daily urine output, using 24-hour urine collection. The mean serum urea con-centration was 16.91 mmol/L and mean serum creatinine was 702 μmol/L. According to the Peritoneal Equiliberation Test (PET), 8% of the subjects belonged to the high trans-porter category, 44% patients belonged to the high-average transport group, 46% to the low-average category and 2% came in the low transporter category. Our study suggests that the patient characteristics and demographic para-meters seen in the Saudi population are comparable to those seen in other studies from the Middle East and worldwide, including data collected from Canada, New Zealand and Mexico.